Glass: A New Media for a New Era? - Anderson, Patrick; Black, Richard; Cerkauskaite, Ausra; Chatzieleftheriou, Andromachi; Clegg, James; Dainty, Chris; Diaconu, Raluca; Donnelly, Austin; Drevinskas, Rokas; Gaunt, Alexander; Georgiou, Andreas; Diaz, Ariel Gomez; et al. (10th USENIX Workshop on Hot Topics in Storage and File Systems (HotStorage 18), 2018)
In the foreseeable future, major cloud vendors will need to store multiple zettabytes of data in their cloud storage infrastructure. Like all storage, cloud storage systems need to trade performance for cost, and they currently achieve this by using storage tiers backed by different storage media. The ultimate goal for cloud storage would be to provide zero-cost storage with low access latencies and high throughput. But all the storage media being deployed in the cloud today were created before the cloud existed, and were designed to support many usage scenarios. With cloud storage, the focus is on cost, and storage needs to be designed to be right-provisionable. The limits of what is possible with existing storage technologies are being reached, and a new clean-slate approach is needed for cloud storage. Hence, the time is right to seek out a new physical media to underpin novel storage systems designed exclusively to support the cloud. In Project Silica, Microsoft Research and Southampton University, are exploring whether quartz glass could be the future media for mass storage in the cloud. In this paper, we describe the basis for the technology, and discuss conventional assumptions about storage that we are challenging in Project Silica.